Factors that affect mother-to-child HIV transmission at a university hospital in southern Brazil - Leopoldino, Maria Aparecida Andreza; Chaves, Eunice Beatriz Martin; da Silva, Carmem Lúcia Oliveira; Corleta, Helena von Eye (Clinical and Biomedical Research, 2017)
Objective: To evaluate factors that may interfere in mother-to-child transmission (MTCT) of human immunodeficiency virus (HIV). Method: A historical cohort study with a sample of 299 HIV-infected mothers and their newborns who delivered at the Obstetric Center of the Hospital de Clínicas de Porto Alegre, southern Brazil, from January 2010 to December 2014. Results: Of the 299 newborns of HIV-infected mothers, 3.7% (n = 11) were infected. Of those, 90.9% (n = 10) were born by cesarean section; 90.9% (n = 10) had ≥ 37 weeks; 54.6% (n = 6) received zidovudine starting within the first 4 hours after birth; and 45.4% (n = 5) received zidovudine and nevirapine. Four women whose newborns were infected with HIV had syphilis during pregnancy (36.4%). Poor adherence to highly active antiretroviral therapy (HAART) (p < 0.003), viral load ≥ 1000 copies/mL or ignored in the third trimester (p < 0.000), and CD4 count < 500 cells/mm3 in the third trimester (p < 0.046) were significantly associated with an increased risk of MTCT. Conclusion: Lack of control of risk factors may contribute to unfavorable rates of MTCT of HIV. Keywords: Risk factors; infectious disease transmission; vertical transmission; acquired immunodeficiency syndrome